2017
DOI: 10.1016/j.jpubeco.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The pros and cons of sick pay schemes: Testing for contagious presenteeism and noncontagious absenteeism behavior

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 95 publications
2
66
0
2
Order By: Relevance
“…Stearns and White (2018) found decreases in absences when examining PSL mandates in Washington, D.C. and Connecticut. This is consistent with Pichler and Ziebarth (2017), which identified a negative correlation between PSL and regional-level influenza rates, suggesting PSL may reduce presenteeism. There is also a small descriptive literature on the direct association between PSL, absenteeism, and health care utilization that primarily makes use of cross-sectional data (Ahn & Yelowitz, 2016;Bhuyan et al, 2016;DeRigne, Stoddard-Dare, & Quinn, 2016;Klein, 2016;Vicente, 2017).…”
supporting
confidence: 88%
“…Stearns and White (2018) found decreases in absences when examining PSL mandates in Washington, D.C. and Connecticut. This is consistent with Pichler and Ziebarth (2017), which identified a negative correlation between PSL and regional-level influenza rates, suggesting PSL may reduce presenteeism. There is also a small descriptive literature on the direct association between PSL, absenteeism, and health care utilization that primarily makes use of cross-sectional data (Ahn & Yelowitz, 2016;Bhuyan et al, 2016;DeRigne, Stoddard-Dare, & Quinn, 2016;Klein, 2016;Vicente, 2017).…”
supporting
confidence: 88%
“…Studies have found that workers who lack paid sick leave are 1.5 times more likely to go to work contagious (Smith & Kim, 2010) and less likely to see a health care provider when sick (Cordoba & Aiello, 2016). Moreover, research has also born out the effectiveness of paid sick leave in reducing community spread of respiratory illness (Kumar et al, 2012;Zhai et al, 2018) and annual influenza rates (Kumar et al, 2013;Pichler & Ziebarth, 2017). The ability to stay home when sick reduces the spread of respiratory and other infectious illnesses to coworkers (Drago & Miller, 2010) thereby reducing productivity losses (Abay Asfaw et al, 2017), and decreasing the risk of spreading illness to customers and clients (Hsuan et al, 2017).…”
Section: Paid Sick Leave When the Economy Is Openmentioning
confidence: 99%
“…Workers without PSL are more likely to report for work when contagious-a phenomenon often referred to as contagious presenteeism-leading to a spread of disease among coworkers and others. Conversely, providing workers access to PSL has been shown to reduce the spread of contagious diseases (e.g., Pichler, Wen, and Ziebarth 2020;Pichler and Ziebarth 2017).…”
Section: Covid-19 Control: Evidence From Cross-country Regression Analysismentioning
confidence: 99%
“…Our novel finding of the importance of PSL to contact tracing effectiveness, while new for COVID-19, is also not without precedent in the broader literature. The importance of PSL to reduce disease transmission in workplaces and overall disease reproductive rates has been demonstrated for influenza like illnesses (Pichler, Wen, and Ziebarth 2020;Pichler and Ziebarth 2017). Given the particular characteristics of COVID-19-that most workers with mild symptoms face minimal risk from engaging in contagious presenteeism, and that the benefits of accurately disclosing information on exposure and symptoms accrue principally as an externality to other parties-it is logical to expect that payment to help correct incentives will make tracing more effective.…”
Section: Bmentioning
confidence: 99%